Cross-reactive humoral and CD4+ T cell responses to Mu and Gamma SARS-CoV-2 variants in a Colombian population - Martel, Fabiola; Cuervo-Rojas, Juliana; Ángel, Juana; Ariza, Beatriz; González, John Mario; Ramírez-Santana, Carolina; Acosta-Ampudia, Yeny; Murcia-Soriano, Luisa; Montoya, Norma; Cardozo-Romero, Claudia Cecilia; Valderrama-Beltrán, Sandra Liliana; Cepeda, Magda; et al. (Frontiers in Immunology, 2023)
The SARS CoV-2 antibody and CD4 + T cell responses induced by natural infection and/or vaccination decline over time and cross-recognize other viral variants at different levels. However, there are few studies evaluating the levels and durability of the SARS CoV-2specific antibody and CD4 + T cell response against the Mu, Gamma, and Delta variants. Here, we examined, in two ambispective cohorts of naturally-infected and/or vaccinated individuals, the titers of anti-RBD antibodies and the frequency of SARS-CoV-2-specific CD4 + T cells up to 6 months after the last antigen exposure. In naturally-infected individuals, the SARS-CoV-2 antibody response declined 6 months post-symptoms onset. However, the kinetic observed depended on the severity of the disease, since individuals who developed severe COVID-19 maintained the binding antibody titers. Also, there was detectable binding antibody cross-recognition for the Gamma, Mu, and Delta variants, but antibodies poorly neutralized Mu. COVID-19 vaccines induced an increase in antibody titers 15-30 days after receiving the second dose, but these levels decreased at 6 months. However, as expected, a third dose of the vaccine caused a rise in antibody titers. The dynamics of the antibody response upon vaccination depended on the previous SARS-CoV-2 exposure. Lower levels of vaccine-induced antibodies were associated with the development of breakthrough infections. Vaccination resulted in central memory spike-specific CD4 + T cell responses that cross-recognized peptides from the Gamma and Mu variants, and their duration also depended on previous SARS-CoV-2 exposure. In addition, we found cross-reactive CD4 + T cell responses in unexposed and unvaccinated individuals. These results have important implications for vaccine design for new SARS-CoV-2 variants of interest and concern.